IMPLEMENTATION OF THE CONCEPT OF AL-'UQÛD AL-MURAKKABAH ON SHARIA FINANCIAL INSTITUTIONS - Setiadi, Atep (Islamicate Institute, 2017)
This paper is intended to analyze philosophically about the existence of al-'Uqûd al-Murakkabah. This paper focuses its assessment on the opinions of scholars of hadith and fiqh (muamalah), as well as its application in Sharia Financial Institutions. This assessment is important because transactions in the form of a single contract are incapable of responding to the development of contemporary financial transactions that are always in motion and are influenced by the financial industry both nationally, regionally and internationally. Using qualitative methods and literature studies in this study it can be concluded that, first, fiqh muamalah contemporary in hadith traditions related to hybrid contract model there is a ban of two contracts in one transaction (bai'ataini fi bai'atin), ban two agreements in one The agreement (shafqa taini fi shafqatin) and the prohibition of the sale and purchase agreements and the ordering of goods (bay 'and salaf); second, the use of hybrid contracts at the Sharia Financial Institution is directed to the manufacture of al' Uqud al-Mutaqâbilah (Dependent or Conditional Contract).